Innovative Solution of Vertical Axis Wind Turbine, Suitable for Naval Industry Implementation (Numerical Methods and Analythical Calculus). (2015) - Ionescu, Raluca Dora; Szava, Ioan; Vlase, Sorin; Ivanoiu, Mircea; Munteanu, Renata
Abstract: In this paper it is continued an analysis of blade design solutions for small power Vertical Axis Wind Turbines (VAWTs), investigating the best solution for a new design that has as objective the minimisation of vibrations, loads, and augmentation of power. It is investigated a classical Darrieus rotor with a NACA0018 blade profile, and then, it is studied the influence of blade flaps on the performance of the aerodynamic profile, aiming to improve the blade lift curve and the CL /CD ratio. It is concluded that the flaps are proven to be an optimized solution in view of aerodynamic performance of the profile, but only up to a certain angle, and thus, it encourages the further studies regarding their feasibility and their effect on the turbine performance.